2022
DOI: 10.1007/s11027-022-10027-4
|View full text |Cite
|
Sign up to set email alerts
|

Breeding targets for heat-tolerant rice varieties in Japan in a warming climate

Abstract: The breeding of heat-tolerant (HT) varieties is considered an effective adaptation measure to reduce the impacts of global warming on crops. However, little is known about how much heat tolerance needs to be attained in the breeding of HT varieties and by when the HT varieties should be introduced in a warming climate. Here, we assessed the effect of the introduction of HT rice varieties on the incidence of low-quality rice grains (chalky rice grain, CRG, as a result of high temperatures), and formulated a bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The variable TaHD (cumulative temperature above the threshold value 26°C) was found to be a key factor, as reported elsewhere (Nishimori et al, 2020). Some researchers used a different base temperature for different genotypes, assuming that heat tolerance would raise the threshold temperature (Takimoto et al, 2019; Masutomi et al, 2022). We also examined this possibility by varying the base temperature for each HTR, but found that the best model fit was obtained with a base temperature of about 26 °C regardless of HTRs (Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable TaHD (cumulative temperature above the threshold value 26°C) was found to be a key factor, as reported elsewhere (Nishimori et al, 2020). Some researchers used a different base temperature for different genotypes, assuming that heat tolerance would raise the threshold temperature (Takimoto et al, 2019; Masutomi et al, 2022). We also examined this possibility by varying the base temperature for each HTR, but found that the best model fit was obtained with a base temperature of about 26 °C regardless of HTRs (Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have quantified the effects of air temperature and solar radiation on the occurrence of CG in specific conditions (Okada et al, 2011; Masutomi et al, 2015; Takimoto et al, 2019). Masutomi et al (2022) conducted a parameter sensitivity test to demonstrate the importance of CG dependence on temperature in the impacts of climate change on rice grain quality. It remains unclear, however, how much actual cultivars with high HTRs can alleviate the negative impacts of ongoing and projected climate change, which is necessary to develop concrete breeding targets in different regions and global warming levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, agriculture production has incurred global warming impacts due to climate change (Dabi and Khanna, 2018;Ezin et al, 2022;Saud et al, 2022). The effects of global warming and arable land erosion are critical and need thorough attention worldwide for achieving food security (Masutomi et al, 2023). High temperatures adversely affect rice plants sensitive to extreme heat, especially at the flowering stage, which leads to sterility and low grain yield (Jagadish et al, 2010;Kinose et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Breeding of heat-tolerant cultivars validates an efficient approach to reducing the impact of global warming on rice and other major crops (Masutomi et al, 2023). Conventional rice breeding generally employs two main methods: the modified pedigree and recurrent selection (Villegas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%